Nonlinear Sum Operator Equations with a Parameter and Application to Second-Order Three-Point BVPs - Wen-Xia Wang; Xi-Lan Liu; Piao-Piao Shi (Abstract and Applied Analysis)
A class of nonlinear sum operator equations with a parameter on order Banach spaces were considered. The existence and uniqueness of positive solutions for this kind of operator equations and the dependence of solutions on the parameter have been obtained by using the properties of cone and nonlinear analysis methods. The critical value of the parameter was estimated. Further, the application to some nonlinear three-point boundary value problems was given to show the significance of the discussion.